An Analysis of Taman Ayun Temple as a Tourist Attraction Based on the 4A Concept - I Gusti Agung Bagus Suryada; Anak Agung Bagus Bayu Anggawirya; Kadek Putra Santika Narayana (Architectural Research Journal, 2026)
Taman Ayun Temple is one of the grandest temples in Bali, which has been designated as a World Cultural Heritage site by UNESCO since 2012. This designation significantly influenced the tourist attraction dynamics based on the 4A components: attraction, accessibility, amenities, and ancillary services. This study aims to analyze the existing condition of these components within and around the site using a descriptive qualitative methodology. Data were collected through direct field observations and comprehensive surveys conducted by the researcher, alongside literature reviews and in-depth interviews with the temple management. The findings indicate that while the historical attractions, layout, and structural authenticity remain highly appealing and deeply rooted in the Tri Mandala spatial concept, certain challenges exist. Based on the primary survey, issues such as material weathering from natural aging, uneven paving on pedestrian access roads, a lack of comprehensive localized informational signage for facilities, and English communication limitations among local vendors and staff were identified. Continuous periodic maintenance, strategic infrastructural upgrades, and language capacity building are essential to sustaining the site's global prominence and preserving its architectural heritage.